Answer:
see explanation
Step-by-step explanation:
Note there is a common difference d between consecutive terms, that is
d = 7 - (- 3) = 17 - 7 = 27 - 17 = 10
This indicates the sequence is arithmetic with n th term
[tex]a_{n}[/tex] = a₁ + (n - 1)d
where a₁ is the first term and d the common difference
Here a₁ = - 3 and d = 10, thus
[tex]a_{n}[/tex] = - 3 + 10(n - 1) = - 3 + 10n - 10 = 10n - 13 ← explicit formula
The recursive formula allows a term to be found by adding d to the previous term, thus
[tex]a_{n}[/tex] = [tex]a_{n-1}[/tex] + 10 ← recursive formula